PENGARUH PENGANGGURAN TERHADAP TINGKAT KEMISKINAN DI KABUPATEN BERAU: PENGARUH PENGANGGURAN TERHADAP TINGKAT KEMISKINAN DI KABUPATEN BERAU - Rabiatul Adawiyah (Prodi Ekonomi Pembangunan, Universitas Muhammadiyah Berau, 2025)
The purpose of this study was to determine the effect of unemployment on poverty levels in Berau District. The variable used is the poverty variable as the dependent variable, while the unemployment variable is the independent variable. The data used in this research is secondary data in annual form (time series) from 2016 to 2021. The test uses SPSS 25 and the data obtained is taken from the Central Bureau of Statistics (BPS) in Berau Regency. The analytical method used in this study is a simple linear regression model. Based on the research results, it can be seen that there is an insignificant effect, a moderate level of relationship and a pattern of positive relationship between unemployment and poverty levels in Berau Regency which is indicated by a correlation coefficient of 0.412 or 17%. This means that unemployment affects the poverty rate by 17% while the remaining 83% is influenced by other factors. Thus that the hypothesis put forward is rejected.